A first assessment of particle flux over the South Brazil Bight continental slope. (December 2021) - Tura, P.M.; Pilskaln, C.H.; Brandini, F.P.
Abstract: The vertical export of particulate organic carbon (POC) is a key component of the oceanic biological pump, which regulates the distribution of elements associated with primary production in the upper euphotic zone. To better understand how oceanic biogeochemical processes will respond in climate change scenarios, it is necessary to comprehend the mechanisms that regulate the magnitude and variations of POC flux among distinct oceanic domains, including the boundaries between continental margins and oceanic basins. This work is a first assessment of particle flux over the South Brazil Bight continental slope, a tropical western boundary system dominated by the Brazil Current. Total mass flux, and specific carbon, nitrogen and biogenic silica fluxes were measured periodically by two sediment traps installed at 450 m deep over the 900 m isobath, and at 750 m deep over the 2000 m isobath, from November 2016 to September 2017. Due to strong contribution of advected particles, high and extremely irregular fluxes were registered at the 900 m isobath site (mean = 1.1 g m -2 d − 1, stand. dev. ± 2.9 g m -2 d -1 ). The captured material suggests this sediment trap was affected by turbidity flows, which precludes the estimation of the biological pump contribution over this isobath. Over the 2000 m isobath, POC flux (3.7 mg m -2 d -1 ; ±2.5 mg m -2 d − 1 ) followed the seasonal pattern of primary production measured by satellite. POC flux was strongly correlated with biogenic silica content (r = 0.79; p < 0.01). This ballast mineral was more efficient than CaCO3 in transferring carbon from the base of the euphotic zone to 750 m. We suggest intra-seasonal variations found in the POC flux over the 2000 m isobath to be related to Brazil Current instabilities. Measurements of δ 15 N suggest that higher POC flux occurred during subsurface nitrate-based production regimes. A regional exponential export model is proposed, with a mean exponent (b value) of 1.4 (±0.3). Although initial, the results of this work allow us to estimate that 2.2 × 10 12  g C is exported annually over the South Brazil Bight continental slope. Highlights: Time-series measurement of POC, PON, CaCO3, biogenic silica and lithogenic particle fluxes over the South Brazil Bight slope. Inter- and intra-seasonal flux patterns are discussed. Biogenic and lithogenic particle sources are investigated through organic matter indexes. Averaged exponential model for the region and estimated annual export.